Impact of active root zone soil potassium levels on cotton yield and fiber quality under no tillage - Shao, Jingjing; Liu, Aizhong; Dong, Helin; Li, Pengcheng; Sun, Miao; Feng, Weina; Huo, Feichao; Zheng, Cangsong (Frontiers in Plant Science, 2024)
Potassium deficiency significantly hinders cotton growth and development, adversely affecting yield and fiber quality. Applying potassium fertilizer is a common practice to address potassium deficiency in the soil. However, the effectiveness of potassium fertilizer application depends on the appropriate soil potassium levels in cotton fields. This study used a randomized block design with six different soil potassium levels and conducted experiments across 18 micro-zones in the field. This study aimed to investigate the response of cotton yield and quality to different soil potassium levels, which tries to clarify the suitable soil potassium levels for cotton growth, so as to provide practical and effective help for determining the amount of potash fertilizer in cotton field. These results showed that the seedcotton yield was increasing with the soil potassium level increased under no tillage. There were no significant difference among K4, K5 and K6 on seedcotton yield, which were significantly higher than K1 and K2. As soil potassium levels increased, the proportion of autumn boll and the proportion of outer boll also increased, indicating that higher soil potassium levels support better growth and development of cotton in the middle and late stages, leading to increased boll sets and higher yield. Additionally, the available potassium content in the 0-40cm soil layer was significantly correlated with yield and yield parameters but not with fiber quality indices. It is concluded that K4 treatment could provided sufficient potassium to meet the growth and development needs of cotton. Potassium fertilizer application is recommended when the available potassium content in the 0-40cm soil layerfalls below 122.88 mg kg -1 in cotton field.